FREE-RADICAL SCAVENGING ACTIVITY OF SOME FRESH AND REFRIGERATED FRUITS - SOWNTHARIYA, C.; SHANTHI, P (International Journal of Pharma and Bio Sciences, 2015)
The antioxidant and free-radical scavenging activities of five different fruits (Malus sylvestris, L., Psidium gujava, L., Citrus aurantium, L., Punica granatum, L., Achras sapota, L.,) were studied to examine the impact of refrigeration. Two sets of selected fruits were examined for fresh and refrigerated conditions under 10ËšC for 20 days. In the present investigation, it was found that the antioxidant activity was higher in fresh Punica granatum, (61.2 mg/g) and the free-radical scavenging activity was higher in fresh Citrus aurantium, (86.6%). Whereas, all the refrigerated fruits exhibited a drastic decrease in the antioxidant and free-radical scavenging activities ranging from 33.9 to 57 mg/g and 33 to 80% respectively. Therefore, our study clearly indicates, low temperature exposure of fresh fruits for longer time may destroy the nutritive compounds, especially antioxidant, a source that neutralize free-radicals damage.